PENGGUNAAN APLIKASI FORM OFFICE 365 UNTUK MENINGKATKAN SEMANGAT BELAJAR SISWA DALAM PEMBELAJARAN DARING - Mujianingsih Mujianingsih; Padmi Hariningsih (Inteligensi : Jurnal Ilmu Pendidikan, 2021)
The purpose of this study was to determine the increase in students' enthusiasm for learning in class I distance learning at SDN Wiyung I/453 Surabaya. In online learning, an application that supports and is easy to operate for students is needed, namely the Office 365 Form. This application is used to determine student learning outcomes and student responses after learning. The research method used is CAR with the instruments used are tests and observations. The results showed an increase in students' enthusiasm for learning during online learning cycle I and cycle II. Students show high motivation in learning. High enthusiasm for learning resulted in student learning outcomes also experiencing changes for the better. It can be concluded that the use of the Form Office 365 application in online learning can increase student enthusiasm and learning outcomes where in the first cycle 72% of students who do and submit assignments on time increase to 94% in the second cycle.